Análisis e interpretación de estados financieros y toma de decisiones gerenciales en la empresa Negoser Don Gonza S.R.L., año 2020 - Calderón Goicochea, Willian Salvador (2022)
The present investigation called analysis and interpretation of financial statements and managerial decision making in the company Negoser Don Gonza S.R.L., financially allowing to know the economic situation and the company with the purpose of making managerial decisions in the economic life of the company. In the first place, a financial analysis was carried out with the vertical method in order to know their variations in their accounts, then with the horizontal method in order to know their variations in amounts and percentages and their expected results, then an analysis was carried out with financial indicators in order to know the liquidity, working capital, asset turnover, indebtedness and profitability of the company and finally an analysis of decision making was carried out in order to know the right decisions that the company must make. The research is of a non-experimental type at a cross-sectional correlational level with a descriptive methodology that allows the explanation of each variable raised, the results of which are shown verbatim, in charts, tables and graphs. The investigation concludes that the analysis and interpretation of financial statements effectively contributes to the development of the company Negoser Don Gonza S.R.L., to make the right decisions in the economic life of the company.